'A rational solution to a different problem'; understanding the verisimilitude of anti-vaccination communication. Issue 1 (2nd January 2021) - Lander, Daniel; Ragusa, Angela T
ABSTRACT: Despite strong consensus about the benefits of vaccines among global health authorities, opposition to vaccination persists and may be growing. Recent research into anti-vaccination attitudes indicates they are complicated and socially embedded, not simply the result of failure to understand vaccine science. That position is supported by theories from science communication and sociological risk, which posit that divergent views about scientific subjects rarely, if ever, result solely from a deficit of knowledge. This study reconceptualises theories of language construction to reflect sociological understandings, demonstrating how scientific and non-scientific dimensions of the vaccination debate operate according to different 'modes' of communication, each with 'radically different procedures for verification'. Understanding this modal distinction may assist pro-vaccination communicators construct messages that more directly address concerns about vaccination objection currently unattended to by deficit model communication.